Icefall - Kirby, Matthew J., 1976- (Scholastic Press, 2011)
Princess Solveig and her siblings are trapped in a hidden fortress tucked between towering mountains and a frozen fjord, along with her best friend and an army of restless soldiers, all awaiting news of the king's victory in battle, but as they wait for winter's end and the all-encompassing ice to break, acts of treachery make it clear that a traitor lurks in their midst.